Sate Mak Syukur Sebagai Ikonik Kuliner dari PadangPanjang - Salakkokoai, vinsensia; Rimelta, Vela; Eliza, Meria (Institut Seni Indonesia Padangpanjang, 2024)
This study aims to determine whether Sate Mak Syukur can become an icon of culinary tourism in Padangpanjang and to determine the economic impact caused by the presence of Sate Mak Syukur as an icon of culinary tourism in Padangpanjang. This study uses a qualitative writing method, namely observation and interviews. Qualitative research methods are research methods used to research natural object conditions. The results of this study were conducted qualitatively descriptively, namely the data collected in the form of words, pictures and not numbers. In this writing, the author went directly to the field to document the writing process as evidence in the implementation of the writing. One of the informants in this study was the owner or business actor. The results of the writing of Sate Mak Syukur as an icon of culinary tourism in Padangpanjang can be seen from several important aspects. Sate Mak Syukur has succeeded in attracting the attention of both local and foreign tourists, thanks to its distinctive taste and attractive presentation. The uniqueness of the recipe and cooking method that have been passed down from generation to generation make this satay not only food, but also part of the culture and traditions of the Padangpanjang community. The economic impact caused by the existence of Sate Mak Syukur is very positive. This culinary business has created jobs for the local community, from processing raw materials to serving customers. In addition, the increase in the number of visitors who come to enjoy this satay also has an impact on other economic sectors, such as accommodation, transportation, and other small businesses around the location. This writing shows that Sate Mak Syukur plays a role as a tourist attraction that can increase visits to Padangpanjang. With the right promotion and development of supporting infrastructure, Sate Mak Syukur has the potential to become one of the famous culinary destinations in Indonesia.